Ketahanan Beberapa Varietas Unggul Kedelai terhadap Nematoda Puru Akar (Meloidogyne incognita) - Wayan Sukanaya (Jurnal Perlindungan Tanaman Indonesia, 2001)
The aims of this experiment are to find the varieties of soybean which are resistant against root-knot nematode (M. incognita) and to determine its attractancy toward the roots of resistant and susceptible soybean varieties. The experiment was divided into two parts, both parts using Completely Randomized Design. The first part was designed to determine the resistance and the second one to determine attractancy. The experiments were conducted in a green house and Plant Pest and Disease Laboratory, Faculty of Agriculture, Udayana University for 5 months. Of the 23 varieties of soybean tested against M. incognita showed that two varieties (Petek and Rinjani) were moderately resistant, 11 varieties were moderately susceptible and 10 varieties were found to be susceptible. However, none of variety was resistant. While on attractancy of root test of moderately resistant and susceptible variety it was found that M. incognita was more attracted to root of susceptible variety (Ringgit) than to moderately resistant variety (Petek).